Near-infrared diffuse optical characterization of human thyroid using ultrasound-guided hybrid time-domain and diffuse correlation spectroscopies - Fernández Esteberena, Pablo Ricardo (2024)
Thyroid vascularization and hemodynamics become altered in thyroid pathologies and could thus inform diagnostics, therapy planning, and follow-up. However, the current non-invasive monitoring methods available in clinics lack the necessary sensitivity and/or are impractical for large-scale deployment. As a step towards proposing a new modality, we applied the first platform, to our knowledge, designed to do simultaneous measurements of neck anatomy and thyroid microvascular hemodynamics and metabolism in a single probe placement, integrating state-of-the-art near-infrared spectroscopy techniques and clinical ultrasound. A rich dataset was formed with sixty-five subjects (forty-eight females), including eighteen healthy volunteers and forty-seven patients with thyroid nodules, characterizing thyroid tissue and the effects of demographic and anatomical variables while preserving the standard clinical workflow. We have found marked reductions with age and body mass index in thyroid total hemoglobin concentration (THC), tissue oxygen saturation (StO2), and blood flow index (BFi), among others. Patients showed lower THC and BFi than healthy subjects, and the limited sample of malignant nodules showed a higher StO2 than the benign. These findings support the need for personalized clinical approaches.